2021
DOI: 10.2478/asn-2021-0008
|View full text |Cite
|
Sign up to set email alerts
|

Ability of metal trace elements accumulation by Lichens, Xanthoria parietina and Ramalina farinacea, in Megres area (Setif, Algeria)

Abstract: The accumulating ability of the atmospheric Metal Trace Elements (MTE) of two lichenic species thalli; Xanthoria parietina and Ramalina farinacea were evaluated in the region of Megres. The recorded concentrations of MTE (Fe, Cu, Mn, Cd, and Pb) were determined by atomic absorption spectrophotometry (AASF). The ability to accumulate MTE in X. parietina thalli is considerably greater than that of the fruticulous lichen R. farinacea in all stations studied. The general pattern of the elements accumulated in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…The high levels of these elements have been positively correlated with the traffic because vehicle exhaust emissions have a significant role in environmental contamination (De Silva et al 2016;Kirpik et al 2017;Yang et al 2020). Studies on the accumulation of MTE by the plants located in the proximity roads showed a close relationship between levels of heavy metals and the volume of traffic (De Silva et al 2016;Yang et al 2020;Belguidoum et al 2021). In Turkey, Nerium oleander has been used as a biomonitor tool for heavy metal accumulation in intense human activity and heavy road traffic (Banu-Doganlar et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The high levels of these elements have been positively correlated with the traffic because vehicle exhaust emissions have a significant role in environmental contamination (De Silva et al 2016;Kirpik et al 2017;Yang et al 2020). Studies on the accumulation of MTE by the plants located in the proximity roads showed a close relationship between levels of heavy metals and the volume of traffic (De Silva et al 2016;Yang et al 2020;Belguidoum et al 2021). In Turkey, Nerium oleander has been used as a biomonitor tool for heavy metal accumulation in intense human activity and heavy road traffic (Banu-Doganlar et al 2012).…”
Section: Discussionmentioning
confidence: 99%